Spatial analysis and outcomes of reported cases of congenital syndrome associated with Zikav in pregnant women, live births and stillbirths in Porto Velho, Rondônia state in the period from 2015 to 2022 (Research, Society and Development, 2022)
Objectives: The present study aims to describe the spatial and temporal distribution, implications and outcomes of suspected cases of ZIKAV in pregnant women, live births and stillbirths in Porto Velho, Rondônia, Brazil, in the period 2015-2022. Methodology: This is an epidemiological, retrospective study, of descriptive nature and quantitative approach, through the data available in the Sistema de Informação de Agravo e Notificação - SINAN of the Registro de Eventos em Saúde Pública - RESPMicrocefalia, ranging from January 2015 to July 2022. Results: We analyzed 151 suspected cases in pregnant women, of these 58 confirmed, predominantly non-white, young adult, single-pregnancy pregnant women. In relation to live births and stillbirths, there was a higher proportion in males, born of adequate weight, the main congenital change detected was microcephaly and outcome of 18 deaths. Final Considerations: The findings of this study highlight the importance of reducing the rate of virus infection in pregnant women, as well as the implications for the mother-fetus binomial, the need for comprehensive prenatal care, as recommended by the guidelines for women's health care and actions at the level of epidemiological surveillance and sanitation aimed at controlling the Aedes aegypti.